2009
DOI: 10.1111/j.1095-8339.2009.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf morphology and anatomy ofCamelliasectionCamellia(Theaceae)

Abstract: The delimitations of species in Camellia section Camellia have been disputed for many years, resulting from uncertain relationships among species. Leaf morphological and anatomical characters for 54 species and three varieties in this section were investigated to reveal the relationships. Principal component analysis and cluster analysis were conducted using the transformed data for quantitative and qualitative characters from leaf morphology and anatomy. Combining the results of statistical analysis with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Th ese structures are made of projections of the fundamental tissue of the vein, which form cavities or fi ssures with trichomes, and have already been described for the genus (Da Cunha & Vieira 1993/97; Quinteiro et al 2006). Epidermal characters have been used in studies on the relationship of taxa (e.g., Ayodele & Olowokudejo 2006;Erxu et al 2009). Some characteristics of the epidermis are infl uenced by environmental conditions, such as the outline of the anticlinal wall and the shape of the external periclinal wall of the epidermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Th ese structures are made of projections of the fundamental tissue of the vein, which form cavities or fi ssures with trichomes, and have already been described for the genus (Da Cunha & Vieira 1993/97; Quinteiro et al 2006). Epidermal characters have been used in studies on the relationship of taxa (e.g., Ayodele & Olowokudejo 2006;Erxu et al 2009). Some characteristics of the epidermis are infl uenced by environmental conditions, such as the outline of the anticlinal wall and the shape of the external periclinal wall of the epidermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contents of these secondary metabolites vary greatly among different varieties and Camellia species, leading to large differences in tea processing suitability 1,185 . They also differ significantly in several morphological traits (e.g., leaf size) and stress resistance characteristics (e.g., cold tolerance), showing a divergent genetic makeup 50,186 . Therefore, the genome sequence of a single individual of a tea plant variety (e.g., shuchazao or yunkang #10) cannot represent the entire gene pool of tea plants.…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%
“…Stomatal clusters in the genus Camellia are generally with 2-4 stomata and arranged adjacent to subsidiary cells (Ao et al 2007;Erxu et al 2009). Stomata clusters were observed in many Camellia species such as C. jinshajiangica, C. omeiensis, C. polyodonta, C. lanosituba, C. longigyna, C. lapidea, C. phelloderma, C. oligophlebia, C. uraku, C. edithae, C. paucipetala, C. henryana, C. tsingpienensis, etc (Ao et al 2007;Erxu et al 2009). While many species without stomata clusters have also been recorded, such as C. xifongensis, C. hongkongensis, C. brachygyna, C. hibisciflora, C. concina, C. glabsipetala, C. villosa, etc (Erxu et al 2009).…”
Section: Epidermal Cells and Stomatal Apparatusmentioning
confidence: 99%
“…However, these Camellia species are difficult to distinguish based on only macro-morphological characters, because of variations in the size and shape of leaves, as well as the size and shape of reproductive parts even in an infrageneric population or a single individual (Zhao 2019), which leads to misidentifications. Erxu et al (2009) suggested that morphological and anatomical characters, especially the leaf part played an essential role in taxonomy and accurate species identification when there was not much information for flower variation or some species flower infrequently. A study on surveying and comparing the leaf epidermis characteristics of some Camellia species was reported by Ao et al (2007), but this does not generalize to new species continuously being recorded.…”
Section: Introductionmentioning
confidence: 99%